2009
DOI: 10.1042/bsr20080128
|View full text |Cite
|
Sign up to set email alerts
|

Aging increases p16INK4a expression in vascular smooth-muscle cells

Abstract: Alteration of VSMC (vascular smooth-muscle cell) physiology is associated with the development of atherosclerosis and restenosis. We hypothesize that aging up-regulates the expression of p16 INK4a in VSMCs, which may increase the susceptibility of blood vessels to vascular occlusive diseases. Aortic VSMCs were obtained from young and aged mice. Cells from aged mice grew more slowly than those from their younger counterparts. Progression of cell cycle in response to serum stimulation was significantly inhibited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 35 publications
2
10
0
Order By: Relevance
“…3C). This was consistent with studies performed in other tissues besides the retina that showed an age-dependent increase of p16 expression in endothelial cells 30 and vascular smooth muscle cells 31 during aging. Although p16, p53, and p21 are considered canonical biomarkers for cellular senescence, 18 SA-b-gal histochemistry, the most widely used assay for senescence, 32 was also performed in old-age retinas.…”
Section: Cellular Senescence In Old-age Human Retinal Blood Vesselssupporting
confidence: 93%
“…3C). This was consistent with studies performed in other tissues besides the retina that showed an age-dependent increase of p16 expression in endothelial cells 30 and vascular smooth muscle cells 31 during aging. Although p16, p53, and p21 are considered canonical biomarkers for cellular senescence, 18 SA-b-gal histochemistry, the most widely used assay for senescence, 32 was also performed in old-age retinas.…”
Section: Cellular Senescence In Old-age Human Retinal Blood Vesselssupporting
confidence: 93%
“…p16 Ink4A and MTOR are known to be involved in signaling in the aging process and are upregulated with aging. 23,24 In our study, p16 Ink4A and MTOR were downregulated in the lungs and liver (except for MTOR in the lungs) after injection of young exosomes. This result could be designated as a critical response to exosomal injection from young to old mice, which reversed the expression pattern of the representative aging-associated molecules.…”
Section: Discussionsupporting
confidence: 45%
“…To support the direct/indirect relationship of reverse-aging with injected young exosomes, we determined the expression level of previously reported molecular biomarkers for aging, such as p16 Ink4A and TOR. 23,24 IGF1R is involved in metabolic changes in the aging process, and upregulation of IGF1R was reported; 25,26 thus, we also analyzed its expression level following the injection of young exosomes to old mice.…”
Section: Introductionmentioning
confidence: 99%
“…CDKN2a) (Dhawan et al, 2009; Janzen et al, 2006; Krishnamurthy et al, 2006; Molofsky et al, 2006; Rodriguez-Menocal et al, 2009; Wang et al, 2012b). Indeed, p16 INK4a is expressed in the mouse cochlea, demonstrates increased expression with age, and its germline deletion results in proliferative cells in the adult organ of Corti after damage (Cox et al, 2012b; Waldhaus et al, 2012).…”
Section: The More Global Aspects Of Aging Suggest Other Potential mentioning
confidence: 99%